2022
DOI: 10.1097/spv.0000000000001240
|View full text |Cite
|
Sign up to set email alerts
|

Small-Fiber Polyneuropathy Is Prevalent in Patients With Interstitial Cystitis/Bladder Pain Syndrome

Abstract: Interstitial cystitis/bladder pain syndrome is a poorly understood chronic pain condition. While patients experience chronic pain in their bladders and changes to their urinary habits, they also commonly experience widespread pain and issues beyond their bladder. The cause(s) of these symptoms is not well understood. Our research found evidence that patients with interstitial cystitis commonly have damage/thinning to the nerves in their skin, which is associated with being chronically fatigued. This finding ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Often, FM is a comorbid diagnosis in patients with similar chronic pain syndromes like IC/BPS and UCPPS (14). More specifically, patients in the non-bladder centric phenotype in IC/BPS are thought to have more systemic non-urologic symptoms and have been shown in preliminary studies to contain more SFPN+ individuals (5,6). Given the prevalence of SFPN in these co-occurring conditions, it is possible that SFPN may also contribute to the pain aspects of IC/BPS.…”
Section: Sfpn In Fibromyalgiamentioning
confidence: 99%
See 1 more Smart Citation
“…Often, FM is a comorbid diagnosis in patients with similar chronic pain syndromes like IC/BPS and UCPPS (14). More specifically, patients in the non-bladder centric phenotype in IC/BPS are thought to have more systemic non-urologic symptoms and have been shown in preliminary studies to contain more SFPN+ individuals (5,6). Given the prevalence of SFPN in these co-occurring conditions, it is possible that SFPN may also contribute to the pain aspects of IC/BPS.…”
Section: Sfpn In Fibromyalgiamentioning
confidence: 99%
“…One emerging theme within this 'systemic pain disorder' concept in IC/BPS is the presence of small fiber polyneuropathy (SFPN). SFPN has been reported as a common finding in FM and UCPPS, and we have recently reported that approximately one-third of patients with IC/BPS have a confirmed finding of SFPN independent of diabetes mellitus (DM) (6). In this narrative review we describe SFPN and its presumed role in several chronic pain disorders that are directly related to IC/BPS.…”
Section: Introductionmentioning
confidence: 96%